Internationalisation Process of Emerging Market Enterprises - Osorio Puentes, Juan Sebastian (2009)
The characteristics of emerging market firms vary to those of „standard‟ firms. This is because the cultural framework under which the emerging market firms were created taught them how to deal with issues such as corruption and bureaucracy encountered in their own countries. A „standard‟ firm does not possess the know-how to deal with these to the same extent and as a consequence, they have to strive further to succeed in emerging markets. On the other hand, the financial resources for a „standard‟ firm are far superior to emerging market firms which means that developed market firms will find it easier from a financial point of view to internationalise into emerging markets than the other way around. The steps for internationalisation that a firm from an emerging market must follow are similar to those that a „standard‟ firm from a developed country must pursue. The individual characteristics of a firm vary, and this means that issues as method selection are also individual to each firm, but all companies must adhere to some procedures such as market research and investigation of the market. There is a slight variation in the level of knowledge that the firms must have in these areas, as emerging market firms need less knowledge to enter a developed market. Therefore, emerging market firms will not adhere as closely to the logical steps indicated by the Uppsala Internationalisation model. The speed of internationalisation will be higher than that of a „standard‟ firm looking to internationalise into an emerging market. This is because risk is smaller in developed countries which means that emerging viii market firms require less knowledge to enter, and thus, they can penetrate developed markets at a faster pace as they do not feel the need to be as cautious with their investment. The UK market is a viable place for ANALISIS TECNICOS LTD to internationalise its services. It is likely that the investment will not be put under jeopardy by country specific factors such as country risk, and the fact that there is strong competition in this market only shows that there is demand for the products, and market share to be taken away from competitors. If this is managed correctly, the firm will benefit from high returns and in the future the possibility of entering the European market will be closer at hand.